Effect of iron on bovine enamel and on the composition of the dental biofilm formed in situ - Martinhon, CCR; de Moraes Italiani, F. D.; de Magalhaes Padilha, P.; Bijella, MFTB; Delbem, ACB; Buzalaf, MAR (Elsevier B.V., 2006)
Objectives: This study investigated in situ the effect of iron (Fe) on the reduction of demineralization of bovine enamel, as well as on the composition of dental biofilm.Design and methods: Twelve volunteers were included in this blind crossover study, which was conducted in two stages of 14 days each. For each stage, the volunteers received palatal appliances containing four blocks of bovine enamel (4 mm x 4 mm x 2.5 mm). Six volunteers dripped a solution of 15 mmol L-1 ferrous sulphate onto the fragments and the remaining six dripped deionized water (eight times per day). After five minutes, a fresh 20% (w/v) sucrose solution was dripped onto all enamel blocks. During the experimental period the volunteers brushed their teeth with non-fluoridated dentifrice. After each stage, the percentage of surface microhardness change (%SMHC) and area of mineral toss (Delta Z) were determined on enamel and the dental biofilm formed on the blocks was collected and analysed for F, P, Ca, Fe and alkali-soluble carbohydrates. The concentrations of F, Ca and Fe in enamel were also analysed after acid biopsies.Results: There was a statistically significant increase in the P and Fe concentrations in the biofilms treated with ferrous sulphate (p < 0.05), which was not observed for F, Ca and alkali-soluble carbohydrates. The group treated with ferrous sulphate had significantly lower %SMHC and Delta Z when compared to control (p < 0.05).Conclusions: These results showed that ferrous sulphate reduced the demineralization of enamel blocks and altered the ionic composition of the dental biofilm formed in situ. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: dental caries; dental biolfilm; demineralization; iron